The Effect of Job Displacement on Subjective Well-being - Younghwan Song (Institute of Labor Economics (IZA), 2017)
Using matched data drawn from the 2010 and 2012 Displaced Workers Supplements of the Current Population Surveys and the 2010, 2012, and 2013 American Time Use Survey Well-Being Modules, this paper examines the effect of job displacement on various measures of subjective well-being. The results indicate that the effect of job displacement on subjective well-being varies by sex and by measure of subjective well- being: among men job displacement does not affect moment-to-moment subjective well-being but lowers their life evaluation through changes in employment, marital status, and earnings, whereas among women job displacement decreases net affect, mostly by decreasing happiness and increasing pain, sadness, and stress, but does not affect their life evaluation. Among men, those displaced by layoffs, not by plant closings, express lower levels of the Cantril ladder than those not displaced but there is no such difference by cause of displacement among women. The negative effects of job displacement on subjective well-being decrease over time for both men and women.
Keywords: I31; J63; J65; 330; job displacement; subjective well-being; Cantril ladder; net affect